The Trouble and Strife Reader - Joan Scanlon; Deborah Cameron (Bloomsbury Academic, 2009)
This is a collection of the best and most enduring articles published in Trouble and Strife: The Radical Feminist Magazine, during its 20-year life, including pieces by Stevi Jackson, Diana Leonard, Julia Swindells, Sara Scott and Liz Kelly.
English